2013
DOI: 10.3390/nu5083118
|View full text |Cite
|
Sign up to set email alerts
|

A Food Photograph Series for Identifying Portion Sizes of Culturally Specific Dishes in Rural Areas with High Incidence of Oesophageal Cancer

Abstract: Rural areas of the Eastern Cape (EC) Province, South Africa have a high incidence of squamous cell oesophageal cancer (OC) and exposure to mycotoxin fumonisin has been associated with increased OC risk. However, to assess exposure to fumonisin in Xhosas—having maize as a staple food—it is necessary to determine the amount of maize consumed per day. A maize-specific food frequency questionnaire (M-FFQ) has recently been developed. This study developed a food photograph (FP) series to improve portion size estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 15 publications
(24 reference statements)
1
19
0
Order By: Relevance
“…The QFFQ comprised 21 maize-based cultural specific food items and beverages and was accompanied by a portion size food photograph series [11,12]. The recall period of the QFFQ was the past month and response categories included “less than once a month”, “amount per month”, “amount per week” and “amount per day”.…”
Section: Methodsmentioning
confidence: 99%
“…The QFFQ comprised 21 maize-based cultural specific food items and beverages and was accompanied by a portion size food photograph series [11,12]. The recall period of the QFFQ was the past month and response categories included “less than once a month”, “amount per month”, “amount per week” and “amount per day”.…”
Section: Methodsmentioning
confidence: 99%
“…We developed and field tested a novel method to derive portion size distributions for the purpose of developing low cost and simple portion size estimation tools, such as food photo atlases, for use in large-scale dietary surveys. The systematic nature of this method represents an improvement on those reported in the literature for similar use, as previous methods have been largely qualitative in nature, and/or the level of representativeness of the usual range of foods consumed by the target population is questionable [6,9,10,12,14,16].…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of pre-existing data, portion size ranges have been deduced by various means, such as by 66 adapting from local reference data (e.g., dietary guidelines and nationally established standard serving 67 sizes), consulting experts in the catering industry, qualitative consultation with households [9][10][11], or 68 deriving a medium portion size from existing survey data but applying fixed ratios to derive small and 69 large portion sizes [9,12]. In some studies to develop and validate food photo atlases, either very scant or 70 no information was provided on how graduated portion sizes were derived [10,13,14], confirming that 71 this methodological step is often overlooked.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that the greater the number of serving size categories, the smaller the estimation error (36). A complex process is triggered when using photographs to identify the portion size of food during a food interrogation.…”
Section: Discussionmentioning
confidence: 99%